Implementasi Gamifikasi untuk Pembelajaran Mitigasi Bencana Tsunami di Sekolah Dasar Nomor 2 Tanjung Benoa - Suryawan, I Putu Dodi; Gunawan, Putu Wida; Rahayu, Prastyadi Wibawa (STMIK Banjarbaru, 2024)
This research uses a gamification approach for tsunami disaster mitigation education for students of SD No. 2 Tanjung Benoa, using the Game Development Life Cycle (GDLC) method. The iterative nature of the GDLC technique and its alignment with the requirements of educational game development were the reasons for its selection. This gamification application uses a quiz-based interactive snakes and ladders game to increase students' interest and understanding of disaster mitigation. Black Box testing is used in system testing to verify the functionality of the application. The results show how well the gamification application works to increase students' awareness and preparedness in dealing with the tsunami tragedy. It is expected that the use of this technology will be a successful approach in disaster mitigation education in coastal areas.Keywords: Black Box Testing; Game Development Life Cycle; Gamification; Tsunami MitigationAbstrakPenelitian ini menggunakan pendekatan gamifikasi untuk pendidikan mitigasi bencana tsunami bagi siswa SD No. 2 Tanjung Benoa, dengan menggunakan metode Game Development Life Cycle (GDLC). Sifat iteratif dari teknik GDLC dan keselarasannya dengan persyaratan pengembangan game edukasi menjadi alasan pemilihannya. Aplikasi gamifikasi ini menggunakan permainan ular tangga interaktif berbasis kuis untuk meningkatkan minat dan pemahaman siswa terhadap mitigasi bencana. Pengujian Black Box digunakan dalam pengujian sistem untuk memverifikasi fungsionalitas aplikasi. Hasilnya menunjukkan seberapa baik aplikasi gamifikasi bekerja untuk meningkatkan kesadaran dan kesiapan siswa dalam menghadapi tragedi tsunami. Diharapkan penggunaan teknologi ini akan menjadi pendekatan yang berhasil dalam pendidikan mitigasi bencana di wilayah pesisir.Â